Mechanical Properties of Wood Polymer Composites (WPCs) After Prolonged Ultra-Violet (UV) Irradiation Exposure - Afiqah S., N.; Zafiah M. Rus, Anika; Zulhafiz Z, M.; Shahrizan Syah, A.; Hazwanee M. J, Farhana; M., Noraini; Aida I., S. (International Journal of Engineering and Technology, 2018)
This research aims to compare the mechanical properties of WPC made from 30 % of rice husk as fibre and 70 % of polypropylene as polymer with and without prolonged UV irradiation exposure. WPC samples are tested with UV irradiation at 5000, 10000, 15000 and 20000 hours with temperature 50 Â°C and tested with compression test (ASTM D695-15) and tensile test (ASTM D638-02), while physical properties characterization was done by density test (ASTM D792-13) and OM test. The compression and tensile result shows decrease value of mechanical properties due to the presence of chain breaking activity contributed from the process of photo oxidation throughout the UV exposure. The effect of UV exposure also resulted in decrease of WPC samples density value as the longer the exposure, the lower the samples density due to the losses of volatile particle. In conclusion, the weather ability of WPC was observed by prolonged exposure to UV radiation thus highlights the influence of parameters involved in the degradation rate of WPC as to contribute a good guidelines and resolution for the future growth of polymer composite structure. Â Â